Covid-19 and international trade: Evidence from New Zealand - Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2022)
The impact of the Covid-19 pandemic on international trade varies along several dimensions, including the type of product, the size of firm and over time. In this note, I provide evidence of systematic variation in the trade response to the pandemic along another, previously unexplored dimension, the mode of transportation. Analyzing daily data from New Zealand, I find that the value of seaborne exports and imports increases relative to shipments by air during pandemic lockdowns. While this finding is consistent with many explanations, including the sensitivity of trade to external finance, it generally provides support for the importance of frictions on the supply side.
urn:nbn:de:tuda-tuprints-214375
Keywords: F14; I18; 330; coronavirus; pandemic; lockdown; restriction; shipments